Konvergensi Indeks Kualitas Lingkungan Hidup (IKLH) Provinsi di Indonesia Tahun 2017 - 2023 - Assel, Abdurrahman; Dunggio, Iswan; Rahim, Sukirman (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2025)
This study examines whether environmental quality across Indonesian provinces is converging or diverging. We analyze the Environmental Quality Index (EQI) and its three components (Water Quality Index (WQI), Air Quality Index (AQI), and Land Cover Quality Index (LCQ))across 34 provinces from 2017 to 2023 using sigma and beta convergence methods. Using panel data analysis, the coefficient of variation calculations show a two-period pattern. The EQI gap widened in 2017–2019, while after 2019 the gap began to narrow, this case indicating improving equity in environmental quality after RPJMN 2020–2024 implementation. The results of the beta convergence test show that provinces with low EQI values ​​tend to experience faster improvement, for EQI overall, with convergence speed of 24.53% annually and half-life of 2.83 years. However, if an analysis of each component is carried out, it is revealed that WQI is the component with the fastest convergence (λ=31.95%) while AQI is the slower component (λ=19.66%) compared to WQI, while LCQ shows divergence (β=+0.0071, not significant).